The concept of adjusting energy level in maintenance rations for cold weather - D.R. Ames (Kansas Agricultural Experiment Station Research Reports, 1978)
Nutrient requirements for domestic animals (NRC) published by the National Research Council are the best estimates available. For beef cattle, specific tables are listed for animals of different weights and for various stages of the production cycle. Although these values are useful for many situations, there are instances when they should be adjusted. One needed adjustment is energy requirement for maintenance when cattle are exposed to cold and rate of heat production must increase to compensate for increased heat loss. The two factors that determine the rate of heat loss are: (1) the differences between body temperature and environmental temperature, and (2) the amount of insulation provided by fat, hide, and hair.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Energy; Temperature